2016
DOI: 10.1186/s11671-016-1266-3
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Surface Corrosion-Resistant Nanocrystalline Structures on Steel

Abstract: Engineering materials with nanocrystalline structure could be exploited under simultaneous action of mechanical loading and corrosion environments; therefore, their corrosion resistance is important. Surface nanocrystalline structure was generated on middle carbon steels by severe plastic deformation using the method of mechanical pulse friction treatment. This treatment additionally includes high temperature phase transformation and alloying. Using a complex of the corrosive, electrochemical and physical inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Medium carbon steels, such as 45 and 35 steels subjected to surface mechanical pulse friction treatment (MPT) have shown a more complex behavior, because this treatment, which combines SPD and surface alloying, can both increase or decrease the corrosion rate. The authors showed that steel 45 with a higher content of carbon processed using MPT undergoes corrosion more intensively than the steel 35 (79) , which corresponds to the general rule that an increase in the carbon content of steel increases the corrosion rate (80,81) . However, the MPT process in the 45 steel increases the quantity of retained austenite which can influence the corrosion processes of the metal too.…”
Section: Carbon and Alloyed Steelsmentioning
confidence: 85%
“…Medium carbon steels, such as 45 and 35 steels subjected to surface mechanical pulse friction treatment (MPT) have shown a more complex behavior, because this treatment, which combines SPD and surface alloying, can both increase or decrease the corrosion rate. The authors showed that steel 45 with a higher content of carbon processed using MPT undergoes corrosion more intensively than the steel 35 (79) , which corresponds to the general rule that an increase in the carbon content of steel increases the corrosion rate (80,81) . However, the MPT process in the 45 steel increases the quantity of retained austenite which can influence the corrosion processes of the metal too.…”
Section: Carbon and Alloyed Steelsmentioning
confidence: 85%
“…У Фізико-механічному інституті НАН України розроблено технологію механоімпульсної обробки, яка формує НКС на високонавантажених поверхнях деталей машин. Автори (Kyryliv, 2012;Kyryliv et al, 2015;Nykyforchyn et al, 2016) показали підвищення експлуатаційних властивостей деталей за зношування, контактних навантажень, дії агресивних середовищ.…”
Section: вступunclassified
“…Presence of considerable amount of interfaces and higher content of alloying elements in the surface layer reduce the negative influence of hydrogen on material [7]. Besides, surface NCS effects on wetting angles of the surface and weakens its interaction with aggressive medium [8].…”
Section: Introductionmentioning
confidence: 99%